How job crafting behaviors influence the innovative behavior of knowledge workers in the gig economy: based on the organismic integration theory - Song, Linpei; Jo, Sung Jun (Frontiers in Psychology, 2023)
The gig economy is extolled for its potential to stimulate economic and social development. These new opportunities enable knowledge-based gig workers to establish new relationships with enterprises based on their strengths and interests. The significance of job crafting in low-skilled occupations has been demonstrated, but the relationships between job crafting and innovative behavior mechanisms present motivational challenges. This study examines the mediating roles of controlled and autonomous motivation in the relationship between job fabrication and innovative behavior in the context of knowledge workers in the gig economy. The structural model analysis of 283 knowledge workers' responses in China suggested that controlled and autonomous motivation mediates the relationship between job crafting (strengths and interests) and innovative behavior. The findings shed light on the knowledge workers' motivation dilemma in the gig economy, with theoretical implications for research regarding job crafting, motivation, and practice implications about the job crafting and innovative behavior of knowledge workers.